Efeito de produtos à base carbonato de potássio, de óleo essencial de melaleuca+ extrato de alho e de terpenos no controle de Podosphaera xanthii da abobrinha - Duarte, David Ferreira (2020)
Powdery mildew is one of the most severe diseases of zucchini and can cause a reduction of up to 50% in productivity. The search for low-cost products and molecules, which are effective in controlling powdery mildew and are harmless to man and the environment, has grown rapidly. The objective of the present study was to evaluate the efficiency of products formulated based on potassium carbonate (Carbos®), the mixture of essential oil + garlic extract (Melalho®) and terpenes (Botanix Terpex®) in the control of zucchini powdery mildew. The assays were carried out in a greenhouse, using zucchini seeds cv. Caserta, which is susceptible to powdery mildew. The inoculation of the plants occurred naturally, keeping zucchini plants with high severity of powdery mildew inside the greenhouse. The products were sprayed weekly on the plants and their effects compared with control plants and with a recommended fungicide. In this study, four experiments were performed, with the first two evaluating several product concentrations Carbos® (0.0; 0.2; 0.5; 0.8; and 1.1% v/v), Botanix Terpex® (0.0 ; 0.1; 0.4; 0.7; and 1.0%, v/v) and Melalho® (0.0; 0.5; 1.0; 1.5; and 2.0%); in the third experiment, the most effective concentrations were evaluated based on the two previous experiments (Carbos® = 0.0; 0.3; and 1.0% v/v), Botanix Terpex® (0.0; 0.2; and 1.0%, v/v) and Melalho® (0.0; 0.5; and 1.0%), also considering phytotoxicity effects; and in the fourth experiment, the effects of the mixture of the alternative products were assessed [(0.2% Botanix Terpex® + 0.5% Melalho); (0.2% Botanix Terpex® + 0.3% Carbos®); (0.5% Melalho + 0.3% Carbos®); and (0.2% Botanix Terpex® + 0.5% Melalho + 0.3% Carbos®)]. The disease severity was assessed weekly, based on the percentage of leaf tissue covered by the pathogen. Severity data, considering only the diseased leaves, were used to calculate the area under the disease progress curve per diseased leaves (AUDPC/DL). In the first two experiments, it was verified that the reduction of AUDPC was inversely proportional to the concentration of the alternative products sprayed, indicating the concentrations mentioned above for each product used in the third experiment, as well as the mixtures tested in the fourth experiment. In the third experiment, the products Melalho (0.5% and 1.0%) and Botanix Terpex (1.0%) showed the lowest AUDPC/DL, differing significantly from the fungicide. In the assay with mixtures of the tested products, it was found that when comparing them with the control and the fungicide, all mixtures significantly reduced the disease severity. All mixtures were statistically similar in terms of reducing the severity of the disease, which was assessed by using the AUDPC/DL. Mixtures of Botanix Terpex® + Melalho + Carbos® (T+M+C), Botanix Terpex® + Melalho® (T+M) and Melalho + Carbos® (M+C) reduced the severity of the disease by 94.9%, 94.9%, and 94.3%, respectively, while the fungicide reduced the disease by 74.5%. Phytotoxicity problems were observed for Melalho® at concentrations of 1.5% and 2% and Carbos® at concentrations of 0.8% and 1.0%.